Investigasi Niat Pembelian Kembali Pengguna E-Commerce dari Perspektif Kualitas Layanan dan Teori Ekspektasi-Konfirmasi - Bagas Putra Pradana (Jurnal Informasi dan Teknologi, 2022)
Most existing research concerning e-commerce in developed countries that have adopted information technology earlier than developing countries, such as Indonesia. The purpose of this study is to know the critical components of e-commerce service quality that can affect the level of customer satisfaction and loyalty in developing countries such as Indonesia using dimensions that researchers have tested in developed countries. The Smart Partial Least Square (SmartPLS 3.0) revealed a positive relationship among service quality, confirmation, satisfaction, and repurchase intention. A positive and significant correlation was also found between website design, information usefulness, privacy & security towards service quality. On the other hand, fulfillment and ease of ordering produced an insignificant relationship with service quality. Practical suggestions for promoting e-commerce in developing countries are provided.